RELATIONSHIP BETWEEN THE MOTHER LEVEL OF EDUCATION SUCCESS BREASTFEEDING EXCLUSIVE IN MELATI INTEGRATED SERVICE CENTER BETENG VILLAGE SUBDISTRICT JATINOM DISTRICT OF KLATEN - Siti Istiqomah; Ilham Musba; Maryanti . (STIKES DUTAGAMA KLATEN, 2015)
Background : Exclusive breastfeeding is influenced by several factors such as aspects understanding, nutritional, educational aspects, immunological, psychological, intelligence, cost and delay pregnancy. The low level of understanding of the importance of breastfeeding during the first 6 months of birth due to lack of information and knowledge possessed by mothers about everything plus nutritional value and benefits contained in breast milk. Objective : To determine the relationshipbetween the mother's level of education on exclusive breastfeeding success in the MelatiIntegrated Service Center Beteng Village Subdistrict Jatinom District of Klaten. Research Methods : This study was a cross sectional analytic study. The population in this research were all mothers with infants aged 6 -24 months in Integrated Service Center in the Beteng Village Subdistrict Jatinom District of Klaten 38 people.The sample in this research as many as 30 people. Instrument research angket, chi square analysis of the data. The results : of the study maternal characteristics maternal age 20-35 years, parity primiparous and housewives. Mother's education level in the Integrated Service Center Beteng VillageSubdistrict Jatinom District of Klaten most basic with the percentage of 53.3%. The success of exclusive breastfeeding in the MelatiIntegrated Service Center Beteng Village Subdistrict Jatinom District of Klaten is succesed on 24 people (80%). Conclusion : There is a relationship with the mother's level of education on exclusive breastfeeding success in the MelatiIntegrated Service Center Beteng VillageSubdistrict Jatinom District of Klaten with value χ 2 = 6.563, p = 0.038 (p <0.05).